Market Day Encourages Social Interaction Among Children Aged 3–4 Years Old: Market Day Mendorong Interaksi Sosial Anak Usia 3–4 Tahun - Ilmiah, Nikmatul; Destiana, Evie (Indonesian Journal of Education Methods Development, 2025)
General Background: Social-emotional development is a key aspect of early childhood growth, requiring children to interact effectively with peers and their surrounding community. Specific Background: Activities that simulate real-life social interactions, such as Market Day, can provide valuable opportunities for practicing social skills. Knowledge Gap: While experiential learning activities are widely discussed, empirical evidence on Market Day’s role in fostering social interaction among very young learners remains limited. Aims: This study investigates the significant relationship between Market Day activities and social interaction skills in children aged 3–4 years at KB-TK Aisyiyah Bustanul Athfal Solokuro. Results: Using a pre-test and post-test design with 20 participants, data were analyzed through normality and homogeneity tests, followed by a paired t-test in IBM SPSS 26.0. Findings showed a significance value of 0.000 ≤ 0.05 and Thitung (9.890) > Ttabel (2.101), indicating a statistically significant improvement in social interaction. Novelty: This study provides quantitative evidence of Market Day’s role in enhancing early childhood social skills in a formal educational setting. Implications: The results suggest integrating structured experiential activities into early childhood curricula to promote social development. Highlights: Quantitative proof of Market Day fostering social interaction in young children. Employs pre-test and post-test design with robust statistical analysis. Supports integrating experiential learning into early childhood curricula. Keywords: Market Day, Early Childhood, Social Interaction, Experiential Learning, Preschool Education